Determinants of financial literacy among working local professional adults in the region of Mecca, Saudi Arabia - Alammari, Salem Mohammed; Hamdan, Hamdino (Academy of Contemporary Islamic Studies (ACIS) Universiti Teknologi MARA, 2020)
Due to the new economic reforms in Saudi Arabia and the introduction of the value added tax, increased the need to enhance the public sector workers financial literacy. Based on the previous studies, the financial literacy among the Saudis in general is low. Therefore, the objective of this study is to examine the degree of financial literacy among the public sector workers in Mecca region, Saudi Arabia. Moreover, the study also aims to identify the determinants of financial literacy among the public sector workers. This study used a descriptive analysis, ANOVA, and multiple linear regression analysis to analyse a primary data collected from 162 public sector worker. The study results reveal above average financial literacy among the public sector workers. ANOVA test indicate that there is a difference among the public sector workers monthly income and level of education groups. Nevertheless, the multiple regression analysis shows that financial behaviour and financial attitude are positively affecting the financial literacy among the public sector workers. This study also recommends some possible ways to enhance, improve, and increase the awareness of, the importance of, and the need for financial literacy among public sector workers.